Taking down of evidence by handwriting in a criminal proceeding under the Malaysian Criminal Procedure Code (CPC), and the Syariah Criminal Procedure (State of Selangor) enactment 2003: Is it mandatory? - Kamaruddin, Abdul Rani; Md Dahlan, Nuarrual Hilal (Malayan Law Journal, 2005)
The essence of criminal justice is to see that justice is seen to be done or to seek the manifest truth. Once justice has been substantially seen to be done, the question that an accused has been prejudiced or for that matter, the prosecution has been put to disadvantage does not arise. In this respect, the chief purpose of procedural law is to lay down the rules that criminal justice officials must follow: That persons must be tried not by arbitrary procedures but in accordance to the process outlined in the law is the basic principle of procedural law. It is a procedural requirement that evidence must be taken down subject to the law of evidence in that generally the evidence sought to be adduced is “relevant” is the best evidence, and is not hearsay, regardless of whether at the close of the case for the prosecution or at the conclusion of the trial; See section 156, 263, 419, 421 422 of CPC; See al-Quran in (i) Sura a-Nahl verse 90 where ‘Allah commands that you be just and fair (adl’)’; al-Quran in Chapter 5, surah al-maidah [the repast] in verse 2 where Allah said, ‘Help ye one another in righteousness and piety but help ye not one another in sin and rancor. Fear Allah: Indeed, Allah is strict in punishment'; Section 3 of the CPC, and also section 3 of the Syariah Criminal Procedure (State of Selangor) Enactment 2003, and Article 5 of the Malaysian Federal Constitution. See for examples sections 173(c), 176 , 267 & 272 of the CPC; See also ss 96 (c), 100, & 113 of the Syariah Criminal Procedure (State of Selangor) Enactment 2003; Sections 5 to 55 of the Malaysian Evidence Act 1950; See also Sections 5 to 42 of the Syariah Court Evidence (State of Selangor) Enactment 2003; Section 61 to 65 of the Evidence Act 1950; See also Sections 48 to 52 of the Syariah Court Evidence (State of Selangor) Enactment 2003.6 See section 60 of the Evidence Act 1950; See also Sections 47 of the Syariah Court Evidence (State of Selangor) Enactment 2003.Taking Down of Evidence by Handwriting in a Criminal Proceeding under the Malaysian Criminal Procedure Code or the Judge must inevitably come to a decision on the evidence of the case in questions. Therefore, the importance of recording the evidence in a form that is intelligible, safe and readily extractable is paramount. Accordingly, the meat of the argument in this article is whether Magistrates and Judges should be tied to using their own handwriting when taking down the evidence or be free to choose other modes in addition or in lieu of handwriting.